Chemical Profiling and Biological Activities of Alphonsea elliptica (Annonaceae) Essential Oil - Wan Mohd Nuzul Hakimi Wan Salleh (Tanjung Malim, 2023)
Chemical Profiling and Biological Activities of Alphonsea elliptica (Annonaceae) Essential Oil by Wan Mohd Nuzul Hakimi Wan Salleh